Investigation Of The Fluid/Structure Interaction In Moulded Underfill Process - Khor, Chu Yee (2013)
The rapid development of portable electronic devices, such as iPad, iPhone, iPod, and laptop, propels the integrated circuit (IC) packaging technology toward miniaturization characterized by high capacity and compactness of IC package. The scaling down of IC package size has given challenges to the engineers and IC designers in maintaining package reliability. In moulded underfill (MUF) process, the interaction between fluid (EMC) and structure (silicon chip and solder bump) yields unintended deformation and stress that may cause defects and reduce package reliability. Thus, the understanding of the FSI phenomenon is essential for the engineers and IC designers to tackle these problems. Therefore, the MUF process considering FSI aspect was the focus of this research. The FSI simulation was performed by finite volume based (FLUENT) and finite element based (ABAQUS) software through the MpCCI coupling technique for the simultaneous analysis. The capability of the software in handling encapsulation problems was examined by comparing the predicted results with previous scholars’ works and the current scaled-up MUF encapsulation processes. The scaled-up MUF encapsulation processes were fabricated in transparent for better visualization of FSI phenomenon, flow and void formation mechanisms. In the simulation, the Castro-Macosko viscosity model was written into UDFs to describe the EMC fluid behaviour. The accurateness of the UDFs has been proven excellent in modelling the rheological fluid behaviour during the encapsulation process.